The relationship between project complexity and project success and the moderating effect of project leadership styles and roles in the construction industry of an emerging economy - Dartey-Baah, Samuel Kwasi (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.